2006
DOI: 10.1024/0301-1526.35.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of infrainguinal revascularization for critical limb ischemia in diabetics with end stage renal disease

Abstract: Diabeticpatients with ESRD attained an acceptable graft patency and limb salvage but they sustained higher perioperative mortality and morbidity and reduced survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
0
18
0
3
Order By: Relevance
“…Thus, the amputation rate observed in our present series is well comparable with recent reports on surgical revascularization in CLI patients with RI. 29,30 O'Hare analyzed 9932 patients undergoing surgical revascularization for PAD in VA hospitals. 3 In total, 11% of patients in that study underwent major lower extremity amputation within 1 year after surgical revascularization: 10% of patients with normal renal function, 11% of patients with moderate RI, 12% of patients with severe RI, and 29% of patients receiving dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the amputation rate observed in our present series is well comparable with recent reports on surgical revascularization in CLI patients with RI. 29,30 O'Hare analyzed 9932 patients undergoing surgical revascularization for PAD in VA hospitals. 3 In total, 11% of patients in that study underwent major lower extremity amputation within 1 year after surgical revascularization: 10% of patients with normal renal function, 11% of patients with moderate RI, 12% of patients with severe RI, and 29% of patients receiving dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Such a risk increased dramatically along with CKD classes (CKD class 3: rr 1.62; CKD class 4: rr 2.85; CKD class 5: rr 3.75). Indeed, such a mortality risk is particularly high after lower limb revascularization as pooled analysis of surgical series showed a 30-day mortality rate of 5% (4), and some more recent studies including endovascular treatment reported immediate mortality rates of about 10% (14,15). Even more dramatic is the increased risk of late mortality in these patients, which suggests that CLI is a malignant condition in ESrD patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is now accumulating experience with PTA, which confirms that the technique yields favourable results in patients with critical limb ischaemia [19]. By-pass graft surgery has also been extensively practised [6,20,21]. Since atherosclerosis mainly affects the infra-popliteal arteries, by-pass grafting usually has to be performed to distal arteries, such as the dorsalis pedis artery [20,21].…”
Section: Established Treatment Of Ischaemiamentioning
confidence: 93%
“…By-pass graft surgery has also been extensively practised [6,20,21]. Since atherosclerosis mainly affects the infra-popliteal arteries, by-pass grafting usually has to be performed to distal arteries, such as the dorsalis pedis artery [20,21]. In a recent cohort study of patients with critical ischaemia, revascularisation by either of the 2 modalities was feasible in most cases and succeeded in a low rate of early major amputation [22].…”
Section: Established Treatment Of Ischaemiamentioning
confidence: 98%